2019
DOI: 10.1007/s10967-019-06772-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiolytic degradation of hydrophilic PyTri ligands for minor actinide recycling

Abstract: The 2,6-bis[1H-1,2,3-triazol-4-yl]-pyridine (PyTri) chelating unit has already shown promising properties for application to advanced hydrometallurgical processes aimed at recovering minor actinides from highly active raffinate. Radiolytic stability is an undeniable key requirement for chemicals involved in highly radioactive solutions partitioning, since radiolysis can have a huge impact on system safety and performances. In this work, the radiolytic degradation of two hydrophilic PyTri complexing agents was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 45 publications
(49 reference statements)
2
13
0
Order By: Relevance
“…It was concluded that the PyTri chelating unit should not present neither hydrolytic nor radiolytic degradation. This is coherent with FT-Raman results, since the intensities of the Raman bands referred to vibrational modes of the aromatic moiety of the ligands remain unchanged 51 .…”
Section: Degradation Of Irradiated Solutionssupporting
confidence: 85%
See 3 more Smart Citations
“…It was concluded that the PyTri chelating unit should not present neither hydrolytic nor radiolytic degradation. This is coherent with FT-Raman results, since the intensities of the Raman bands referred to vibrational modes of the aromatic moiety of the ligands remain unchanged 51 .…”
Section: Degradation Of Irradiated Solutionssupporting
confidence: 85%
“…NMR spectroscopy was employed with the purpose of confirming the preliminary results already obtained by ESI-MS and FT-Raman, whose results have already been published elsewhere 51 . The NMR spectra are reported in SI.…”
Section: Degradation Of Irradiated Solutionsmentioning
confidence: 76%
See 2 more Smart Citations
“…PTD also features sought-aer characteristics which make it suitable for industrial application: water solubility and complete incinerability. [17][18][19] In addition, PTD has been intensively studied as terdentate chelating agent for different applications such as catalysis or biomedical application 20 both in supramolecular and coordination chemistry. 21 From a fundamental point of view, the full three-dimensional characterization of PTD, despite its important role in complex formation, remains still unpublished.…”
Section: Introductionmentioning
confidence: 99%